An improved technique for the assessment of venom-induced haemorrhage in a murine model. (1st December 2017) - Jenkins, Timothy P.; Sánchez, Andrés; Segura, Álvaro; Vargas, Mariángela; Herrera, María; Stewart, Trenton K.; León, Guillermo; Gutiérrez, José María
Abstract: Haemorrhage is a common clinical manifestation in envenomings caused by bites from snakes of the family Viperidae. Therefore, knowing the haemorrhagic potential of venoms and the capacity of antivenoms to neutralise this effect are of paramount relevance in toxinology. The most widely used method for quantifying haemorrhage involves the intradermal injection of venom (or a mixture of venom/antivenom) in mice, and the assessment of the resulting haemorrhagic area in the inner side of the skin. Although this method allows a straightforward assessment of the haemorrhagic activity of a venom, it does not account for haemorrhagic lesions having a similar area but differing in the depth and intensity of haemorrhage. We have developed an approach that allows the assessment of both area and intensity of a venom-induced haemorrhagic lesion using computational tools and propose a unit to represent the combination of these two factors as a measure of haemorrhage intensity, namely haemorrhagic unit (HaU). A strong correlation was observed between haemoglobin extracted from a haemorrhagic lesion and the associated HaUs. The method was used to determine the haemorrhagic activity of the venoms of Bothrops asper, Echis ocellatus and Crotalus basiliscus and the haemorrhage neutralising capabilities of the three associated antivenoms. Overall, the ease of use, as well as the time involved in this new method, makes its implementation very feasible in the determination of haemorrhagic activity of venoms and its neutralisation by antivenoms in the murine model. Graphical abstract: Highlights: A new method to quantify local haemorrhagic activity of venoms is described. The method assesses not only the area of haemorrhage but also the intensity. The method uses freely accessible computational tools. The method also allows the study of the neutralisation of haemorrhagic activity by antivenoms.